Division of Data Ownership Between the Individual and the Enterprise That Collects the Data (Asian Business Research, 2022)
More and more cases involve disputes between users and platform providers over the protection of personal information and the ownership of the right to personal information. In the big data era, data is an emerging object of civil rights. The ownership of data is very important to the protection of personal information and data transfer. However, there is no explicit legislation to regulate the ownership. In this regard, the author is of the opinion that the original/underlying personal data shall belong to the user, and the fully anonymized dataset based on the original data shall enjoy the property rights and interests in the context of competition.